Radio frequency (RF) control of red flour beetle (Tribolium castaneum) in stored rapeseeds (Brassica napus L.). (November 2016) - Yu, Daeung; Shrestha, Bijay; Baik, Oon-Doo
Abstract : Absolute and relative mortalities of red flour beetle ( Tribolium castaneum ) infesting the rapeseeds of a small (196.3 cm 3 ) and a large (1766 cm 3 ) volumes during radio frequency (RF) heating (1.5 kW, 27.12 MHz) were determined at different end temperatures (30–80 °C) and initial seed moisture contents (5%, 7%, 9%, and 11% wet basis). 100% absolute and relative mortalities of the adult insects were achieved at 80 °C for the small volume of the seeds at all moisture contents (MCs) and at 60 °C and 9% and 11% MCs, and 70 °C and 5% and 7% MCs for the large volume. Over 80% and 96% of the absolute and the relative mortalities of the adult insects were achieved at over 60 °C for both volumes of the seeds. 100% mortalities of larvae infesting the small and the large volume seeds were achieved at 55 °C at all MCs. Germination, major and minor axes, roundness, colour of the seeds and qualities of the rapeseed oil were not affected significantly by RF treatment temperature at entire MCs. Therefore, a complete mortality of the red flour beetle infesting the rapeseeds with acceptable thermal degradation to qualities of the seeds could be achieved at under 60 °C by the RF treatment with a proper design of RF disinfestation. Highlights: Mortalities of red flour beetle infesting canola seeds by RF heating were obtained. Over 80% and 96% of mortalities of insects were achieved at over 60 °C. 100% mortalities of larvae, eggs, and pupae were achieved at over 55 °C. Qualities of canola seed and oil were not affected significantly by the RF heating. A complete mortality of the insect could be achieved at under 60 °C by RF treatment.